Perspective on the Era of Global Boiling: A Future beyond Global Warming - Teerachai Amnuaylojaroen (Advances in Meteorology)
As the unpredictable nature of the Earth’s climate persists, the scholarly attention dedicated to climate research has undergone a notable transition, shifting its emphasis from the conventional notion of global warming to a greater disconcerting occurrence commonly referred to as “global boiling.” The present article endeavors to elucidate the scientific evidence that posits a discernible alteration in climate patterns, specifically towards an exacerbation of extreme heat events. Furthermore, this study aims to delve into the various factors that are believed to be instrumental in precipitating this noteworthy phenomenon. Furthermore, we engage in a comprehensive examination of the potential ramifications on ecological systems, human communities, and the imperative necessity for proactive measures aimed at both mitigating and adapting to these challenges. This paper endeavors to elucidate the potential issues presented by the period of global boiling through a thorough examination of existing research and data. Furthermore, it seeks to underscore the significance of concerted efforts to effectively tackle this pressing matter.